Arsenic contamination in GBM plains with a focus on Bihar, India: risks and remediation - Nishita Ivy (Discover Environment)
Abstract Groundwater arsenic (As) contamination is a serious environmental and public health concern worldwide. Adverse health outcomes and poor socio-economic conditions made the contamination scenario worse in the Ganga–Brahmaputra–Meghna (GBM) plains, including Bihar state of India. Recently, the population in Bihar has been experiencing high risks of As exposure from drinking water and foods. However, limited studies are available on groundwater As, its transfer to foodstuffs, and associated health effects for the state. Therefore, this review addressed the current scenario of groundwater As, its subsequent transfer in edible plants, and associated health effects on the local population of Bihar. Apart from other remediation options, the potential of bioremediation was also explored as an effective way of As mitigation. Among the four major agro-climatic zones in Bihar, high numbers of As-affected districts are situated in Zone I and Zone II, respectively. The risk of cancers in human organs like skin, bladder, kidney, liver, and lung has been increasing in the state with the prevalence of high As levels, particularly near and north of the Ganga river. A significant correlation was found between maximum As levels in water and blood. Food items particularly wheat could play a significant role in As exposure apart from drinking water. Still, As mitigation approach is solely focused on drinking water, and measures are necessary to reduce exposure from foodstuffs. Although several indigenous bacterial strains were found promising for bioremediation in Bihar, further understanding is essential for their application. Moreover, effective policies and regulations are needed based on spatial variation in contamination, socio-economic conditions, and demographic characteristics.